Avian schistosomes from the south american endemic gastropod genus Chilina (Pulmonata, Chilinidae), with a brief review of South American schistosome species - Flores, Verónica Roxana (2015)
Our current knowledge of avian schistosomes from South America is scarce in all respects, including species and genericdiversity, their life cycles, patterns of host use, potential to cause dermatitis outbreaks, and evolutionary affinities. As a step towardsaddressing this shortcoming, the goal of this study was to provide discrete reference points relating to snail hosts, locality records,morphological attributes, sequence for nuclear 28S and ITS, and partial mitochondrial cox1 genes, and phylogenetic relationships forschistosome cercariae recovered from different species of Chilina, which are gastropods endemic to South America. In total, 1,308snails belonging to 6 species of Chilina were collected from 12 localities across Argentina. Thirty-eight snails (2.9%) had schistosomeinfections. Our data indicate the presence of 3 lineages of Chilina-transmitted schistosomes, all of which group within the major avianschistosome clade. However, none of the lineages grouped within or as sister to other known avian schistosome genera in the tree,indicating they probably represent undescribed genera. The relationships of these schistosomes from Chilina spp. are discussed inrelation to their position in the global schistosome phylogenetic tree.